2019
DOI: 10.1016/j.cjtee.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the efficacy of gentamicin-coated intramedullary interlocking nail versus regular intramedullary interlocking nail in Gustilo type I and II open tibia fractures

Abstract: PurposeOpen tibia fracture is prone to infection, consequently causing significant morbidity and increasing the hospital stay, occupational loss and onset of chronic osteomyelitis. Intramedullary nailing is one choice for treating tibia shaft fractures. To improve the delivery of antibiotics at the tissue-implant interface, many methods have been proposed as a part of prophylaxis against infection. This study was conducted to study the role of gentamicin-impregnated intramedullary interlocking (IMIL) nail in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…The literature search, excluding duplicates, resulted in 32 records ( Figure 1 ). After a full text review, eight studies were included for final analysis ( Table 1 ) [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. According to Oxford’s Level of Evidence, there was one study at level II, one study at level III, and six studies at level IV.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search, excluding duplicates, resulted in 32 records ( Figure 1 ). After a full text review, eight studies were included for final analysis ( Table 1 ) [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. According to Oxford’s Level of Evidence, there was one study at level II, one study at level III, and six studies at level IV.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, two case reports were retrieved and included in the review [ 18 , 19 ]. No studies reported a control population treated with a nail without gentamicin coating, except for Pinto et al, which performed a prospective study with randomization by alternate allocation of the patients [ 24 ]. Out of these studies, 203 patients were retrieved; the median age was 45 ± 13 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations